(untitled) (CIPEEX, 2025)
This abstract aimed to highlight the risks associated with self-medication for weight loss purposes. The use of medications and supplements without the advice of a health professional can have serious health consequences, including adverse effects, dangerous drug interactions, and chronic damage to the body. However, many people, in search of quick results and miraculous solutions, resort to the indiscriminate use of off-label medications, disregarding the risks involved. Such conduct can result in serious health problems, compromising safety and well-being. Some drugs such as semaglutide, metformin hydrochloride and orlistatinhave been used. Semaglutide, sold as the brand names Ozempic®, Wegovy® and Rybelsus®, is used in the treatment of type 2 diabetes mellitus that helps reduce blood sugar levels. This active ingredient has been widely consumed for quick weight loss purposes without advice from a health professional. Metformin hydrochloride, sold with Glifage XR®, has the same function as semaglutide, being a drug of choice for oral treatment of type 2 diabetes mellitus. Metformin stimulates protein kinase, which through the activation of adenosine monophosphate, has the function of reducing hepatic glucose production, in addition to reducing glucose absorption in the intestine, also reducing the appetite of patients with type 2 diabetes mellitus. Thus, it has been used indiscriminately to lose weight through self-medication. Finally, orlistatin, marketed as Orlistat®, acts as a long-acting inhibitor of long-acting reversible pancreatic and gastrointestinal lipases. Upon reaching the gastrointestinal lumen, it forms a covalent bond with the serine portion of the active site of gastric and pancreatic lipases. It has no systemic absorption, and the inactivated enzyme is unable to hydrolyze the fat from food, causing about 30% of the fat from the food ingested to be eliminated in the feces. Therefore, it is also widely used without the knowledge and guidance of health professionals. Another important factor concerns access to medicines, most of them do not require a prescription. In view of this, self-medication has been justified by the ease of access to the drug and confidence in the effect of the drug. In summary, in general, self-medication for weight loss purposes has been carried out in an uncontrolled way and without the monitoring of health professionals, which can bring serious consequences and risks to the health of those who seek weight loss and a perfect body in contemporary society.Keywords: overweight; weight loss; self-medication; side effects.